Competitive Interaction of Axonopus compressus and Asystasia gangetica under Contrasting Sunlight Intensity. (17th September 2013) - Samedani, B.; Juraimi, A. S.; Anwar, M. P.; Rafii, M. Y.; Sheikh Awadz, S. H.; Anuar, A. R.
Abstract : Axonopus compressus is one of the native soft grass species in oil palm in Malaysia which can be used as a cover crop. The competitive ability of A. compressus to overcome A. gangetica was studied using multiple-density, multiple-proportion replacements series under a glasshouse and full sunlight conditions in a poly bag for 10 weeks. A. compressus produced more dry weight and leaf area when competing against A. gangetica than in monoculture at both densities in the full sunlight and at high density in the shade. Moreover, the relative yield and relative crowding coefficients also indicated A. compressus is a stronger competitor than A. gangetica at both densities in the full sunlight and high density in the shade. It seemed that A. gangetica plants in the shade did not compete with each other and were more competitive against A. compressus as could influence A. compressus height in the shade. It is concluded that although suppression of A. gangetica by A. compressus occurred under full sunlight, irrespective of plant density, this ability reduced under shade as A. compressus density decreased. The result suggests that A. compressus in high density could be considered as a candidate for cover crops under oil palm canopy.